State Measurement and Control Technology of Unmanned Vehicle Based on High-Precision Positioning - Zhongyi Zhao (Hindawi Limited, 2021)
For the unmanned vehicle system, the state measurement and control technology is one of the key links to realize the real unmanned vehicle. Based on RTK positioning technology and ultrashort wave spread spectrum communication technology, the key technologies of special vehicles with unmanned automatic operation are studied, and a set of state monitoring and control system of special vehicles with unmanned automatic operation is developed. Through the experimental research, the unmanned vehicle state monitoring and control system can better complete the functions of vehicle location and electronic map display and meet the design requirements. The research results provide technical support for the practical application of special vehicles with unmanned automatic operation.